Social anxiety under load: the effects of perceptual load in processing emotional faces - Soares, Sandra C.; Rocha, Marta; Neiva, Tiago; Rodrigues, Paulo; Silva, Carlos F. (Frontiers in Psychology, 2015)
Previous studies in the social anxiety arena have shown an impaired attentional control system, similar to that found in trait anxiety. However, the effect of task demands on social anxiety in socially threatening stimuli, such as angry faces, remains unseen. In the present study, fifty-four university students scoring high and low in the Social Interaction and Performance Anxiety and Avoidance Scale (SIPAAS) questionnaire, participated in a target letter discrimination task while task-irrelevant face stimuli (angry, disgust, happy, and neutral) were simultaneously presented. The results showed that high (compared to low) socially anxious individuals were more prone to distraction by task-irrelevant stimuli, particularly under high perceptual load conditions. More importantly, for such individuals, the accuracy proportions for angry faces significantly differed between the low and high perceptual load conditions, which is discussed in light of current evolutionary models of social anxiety.